KARAKTERISTIK KIMIA DAN ORGANOLEPTIK TEH HERBAL KULIT PALA (Myristica fragrans Houtt) DENGAN VARIASI LAMA PENGERINGAN MATAHARI - Siti Maryam Eka Putri Kaplale; Syane Palijama; Rachel Breemer (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
This study aims to determine the appropriate sun drying time for the chemical and organoleptic characteristics of the herbal nutmeg peel. This study used a completely randomized design with 4 levels of sun drying treatment, including: M1 = 10 hours, M2 = 15 hours, M3 = 20 hours, M4 = 25 hours, and repeated 3 times. The results showed the best treatment was sun drying for 25 hours which had 16.74% phenol content, 6.82% moisture content, 32% yield, 10.84% ash content, 58.89% fiber content, and had an average organoleptic test value and organoleptic characteristics of both the hedonic test and the hedonic quality test respectively include: color with a scale value of 3.75 (very like) and 3.58 (very brownish yellow) and taste with a scale value of 3.08 (like) and 3.03 (taste of nutmeg)